CFD Simulation of a Semi-Submersible Floating Wind Platform in Waves. Balancing Accuracy and Efficiency in Simulation of Wave-Structure Interaction - Larnert, Johanna (My University, 2025)
Offshore wind power is a promising solution for large-scale renewable energy production, offering benefits such as abundant offshore space and higher energy output. One type of floating platform is semi-submersibles, which combine buoyancy stabilization with catenary mooring systems. This thesis presents the development of a numerical model of the YFloat semi-submersible floating offshore wind platform using the CFD software StarCCM+, intending to achieve a balance between computational efficiency and solution accuracy. To support model development, initial wave simulations were conducted without the floater to investigate mesh requirements for accurately capturing wave-induced currents and wave heights. The results indicated that capturing the wave-induced current required a fine mesh with at least 25 cells per wave height and 132 cells per wavelength, while wave heights could be represented adequately with a significantly coarser mesh. Consecutive full-scale simulations included the floater and were validated against experimental model test data. A free decay simulation was used to confirm the floater’s dynamic properties, showing less than 5 % deviation in rotation around the x-axis compared to test results. Simulations in regular waves focused on the spatial and temporal resolution influence on motion responses and wave height. The best compromise between accuracy and efficiency was achieved with 10 cells per wave height and a time step of Δt = 0.02 s. This configuration required 2.8 hours of simulation time, saving 7.3 hours compared to the finest spatial resolution, which took 10.1 hours (a 72.3% reduction), and 9.7 hours compared to the finest temporal resolution, which took 12.5 hours (a 77.6% reduction). The numerical results showed strong agreement with experimental data, validating the CFD model.
Keywords: Computational fluid dynamics; floating offshore wind; semi-submersible